The value of reducing cancer risks at contaminated sites: Are more heavily exposed people willing to pay more? - Anna Alberini; Stefania Tonin; Margherita Turvani (Fondazione Eni Enrico Mattei (FEEM), 2009)
We use conjoint choice questions to investigate people's tastes for cancer risk reductions and income in the context of public programs that would provide for remediation at abandoned industrial contaminated sites. Our survey was self-administered using the computer by persons living in the vicinity of an important contaminated site on the Italian National Priority List. The value of a prevented case of cancer is exteuro2.6 million, but this figure does vary with income, perceived exposure to contaminants, and opinions about priorities that should be pursued by cleanup programs.
Keywords: J17; I18; K32; Q51; Q53; 330; Value of a Statistical Case of Cancer; Conjoint Choice Experiments; Contaminated Sites; Abandoned Sites; Reuse; Remediation